The sex ratio of spruce bark beetles - Ips typographus (Coleoptera: Curculionidae: Scolytinae) captured in different types of traps - Marie Zahradníková; Jaroslav Dostál; Petr Zahradník (Journal of Forest Science)
In forest protection, various types of trap systems are used against spruce bark beetles to treat the foci of infested areas. Traditionally, these include pheromone traps, treated trap trees, and recently also the application of Storanet insecticide nets used for the sanitation of infested wood (trees), which also serve as treated trap trees when pheromones are applied, and the Trinet P system, a variation to a treated trap tree - a tripod. On an aluminium tripod, there is a Storanet insecticide net baited with a pheromone dispenser similar to other types of trap systems. The sex ratio proves to be a significant aspect in the assessment of individual types of trap systems. It is more favourable to catch a larger number of female individuals given that they bear the future development of the population. With a higher number of captured male individuals, the number of females per one male in the insect gallery increases, and the population cannot be reduced sufficiently. The results show that all three types of measures can be characterised by a lower ratio of captured males (approximately 40%) and a higher representation of females (around 60%). Differences in individual types of trap systems are insignificant.